Rotary ultrasonic machining of optical K9 glass using compressed air as coolant: a feasibility study - Zhang, Chenglong; Cong, Weilong; Feng, Pingfa; Pei, Zhijian J. (My University, 2013)
Optical K9 glass has been used in a variety of applications, including optics, electronics, thermodynamics, and fluidics. It has been regarded as a difficult-to-cut material because of its superior mechanical properties. Rotary ultrasonic machining (RUM) using cutting fluid has been used successfully to machine many different types of brittle materials, such as ceramics, sapphire, and optical K9 glass. Dry machining has been successfully employed in the machining of some materials. However, there are no reported investigations on the RUM of optical K9 glass using compressed air as a coolant. This paper, for the first time, investigates the RUM of optical K9 glass using compressed air as a coolant. The experimental investigations focus on the effects of the input variables (ultrasonic power, spindle speed, and feedrate) on the output variables (edge chipping size, cutting force, surface roughness, and ultrasonic power consumption).
Keywords: Rotary ultrasonic machining; Optical K9 glass; Compressed air; Drilling; Processing performance